The strong-weak coupling symmetry in 2D Φ⁴ field models - Shalaev, B.N. (Condensed Matter Physics, 2005)
It is found that the exact beta-function β(g) of the continuous 2D gΦ⁴ model possesses two types of dual symmetries, these being the KramersWannier (KW) duality symmetry and the strong-weak (SW) coupling symmetry f(g), or S-duality. All these transformations are explicitly constructed. The S-duality transformation f(g) is shown to connect domains of weak and strong couplings, i.e. above and below g*. Basically it means that there is a tempting possibility to compute multiloop Feynman diagrams for the β-function using high-temperature lattice expansions. The regular scheme developed is found to be strongly unstable. Approximate values of the renormalized coupling constant g* found from duality symmetry equations are in an agreement with available numerical results. Знайдено, що точні бета-функції β(g) неперервної 2D gΦ⁴ моделі володіють двома типами дуальної симетрії, а саме дуальною симетрією Крамерса-Ванньє (КВ) і симетрією сильно-слабкого (СС) зв’язку f(g), або S-дуальністю. Усі ці перетворення конструюються явно. Показано, що S-дуальне перетворення f(g) зв’язує домени слабкого і сильного зв’язку, тобто вище і нижче g*. По суті це означає, що є приваблива можливість обчислювати багатопетлеві діаграми Фейнмана для β-функцій, використовуючи високотемпературні ґраткові розклади. Знайдено, що розвинута регулярна схема є дуже нестійкою. Знайдені з рівнянь дуальної симетрії наближені значення g* узгоджуються з доступними чисельними результатами.